Education Management Reform Strategy for Enhancing Quality Citizenship in Cambodia - Hang-Chuon, Naron; Siribanpitak, Pruet; Usah, Chayapim (Journal of Education Studies, Chulalongkorn University, 2019)
The objectives of this research were: 1) to identify the needs in education management reform for enhancing quality citizenship in Cambodia through needs assessment; and 2) to develop education management reform strategies for enhancing quality citizenship in Cambodia. Data collection was employed with 710 participants. The collected data were analyzed using descriptive statistics and PNI modified calculation. The findings of the study revealed that for the first objective the highest priority needs in education management reform for enhancing quality citizenship are educationfinancialmanagementreform, followed by administrative and general management reform, academic management reform, and personnel management reform. The strategies and sub-strategies involved the following: 1) Education financial management reform: 1.1 Increase financial autonomy and accountability. 1.2 Conduct an education budget audit for quality citizenship. 1.3 Link the budget to education policies. 2) Administrative and general managementreform: 2.1 Ensure community involvement in school management. 2.2 Implementschool-based management. 2.3 Carry out an education policy and education strategic plan. 3) academic management reform: 3.1 Conduct regular assessments of students. 3.2 Improve teaching methods. 3.3 Integrate the concept of quality citizenship into the school curriculum and textbooks. 4) Personnel managementreform: 4.1 Provide in-service training, focusing on teaching methods and mentoring program. 4.2 Increase teacher qualifications. 4.3 Implement teacher performance assessment.